GRAMMATICAL AND CONTEXTUAL CLASSIFICATIONS OF CODE SWITCHING USED BY AGNES MONICA IN “OBAMA DAN INDONESIA EKSKLUSIF” TALK SHOW - EFFENDY, ELLA HESTY (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Code Switching, Bilingualism, Obama dan Indonesia Eksklusif Talk Show,Agnes monica, Grammatical Classification, Contextual Classification.To deliver their ideas, people use certain languages to communicate with others. It is not rarely found that people can speak more than one languages. Bilingual and Multilingual tend to use certain codes that they are able by inserting different language when they speak. They switched since they have certain intention, purpose or reason.This study was conducted to find out the using of code switching based on position, to identify the reasons and the factors affecting the using of code switching by Agnes Monica in Obama dan Indonesia Eksklusif talk show. The writer chose Agnes Monica as her object study because as public figure she often uses code switching.This study used qualitative approach and document analysis since the data were collected and analyzed in sentence form. The data were the transcription of Obama dan Indonesia Eksklusif talk show. In this study the writer used Blom & Gumperz (1971) and Holmes (2001) theories to analyze the data.The writer found the type of code switching used by Agnes Monica based on position; 1 inter-sentential code switching and 7 intra-sentential code switching, 3 combination of intra-sentential code switching and inter-sentential code switching, 2 combinations both of intra-sentential code switching and tag code-switching, while for code switching based on motivation that divided into 2 parts, are 4 Situational switching and 7 Metaphorical switching. 2 combinations of Metaphorical and Situational code switching. While for influential factors are Ends, Act Sequence and Key.The writer suggests the next researcher to analyze the use of code switching in real life such as in campaigns or social media.